Remaking Kurosawa - Martinez, Dolores. author. aut Link
XIX, 225 p.
Keywords: Through the lens of Akira Kurosawa's films, Martinez dissects the human tendency to make connections in a pioneering attempt to build a bridge out of diverse materials: the anthropology of Japan, film studies, and postmodern theory.